2020
DOI: 10.4269/ajtmh.19-0359
|View full text |Cite
|
Sign up to set email alerts
|

Improving Lives in Three Dimensions: The Feasibility of 3D Printing for Creating Personalized Medical Aids in a Rural Area of Sierra Leone

Abstract: The aim of this feasibility study was to investigate how a 3D printer could be put to its best use in a resourcelimited healthcare setting. We have examined whether a 3D printer can contribute to making prostheses, braces, or splints for patients who underwent major limb amputation because of complex wounds, for example, due to burns and subsequent scarring, accidents, conflicts, or congenital abnormalities. During a 3-month period, we investigated the benefits of customized, 3D-printed arm prostheses, splints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 12 publications
1
45
1
1
Order By: Relevance
“…At the start of the 3D printing Sierra Leone project, we quickly realised that the demands of Sierra Leonean amputees are different from those in Europe. In our earlier work focusing on arm prostheses, it became clear that aesthetics plays an important role [23]. All participants indicated that aesthetics was just as important as functionality.…”
Section: Importance Of Aesthetics In Prosthesis Productionmentioning
confidence: 92%
See 1 more Smart Citation
“…At the start of the 3D printing Sierra Leone project, we quickly realised that the demands of Sierra Leonean amputees are different from those in Europe. In our earlier work focusing on arm prostheses, it became clear that aesthetics plays an important role [23]. All participants indicated that aesthetics was just as important as functionality.…”
Section: Importance Of Aesthetics In Prosthesis Productionmentioning
confidence: 92%
“…In collaboration with the 3D laboratory at the Radboud University Medical Centre, a 3D lab was set up in the Masanga Hospital in Sierra Leone [21,22]. In 2018 and 2019, a feasibility study was performed to investigate the use of a 3D printer in a resource-limited healthcare setting [23]. With this relatively simple technology, low-cost 3Dprinted arm prostheses and other medical aids were produced within a short time.…”
Section: Introductionmentioning
confidence: 99%
“…Although patients were involved in the design process, designs were kept simple to enable reproducibility. The design and manufacturing of the prosthesis have been described in detail before by Van der Stelt et al, 2020 andby Van Gaalen et al (2021). The designs were made in close collaboration with a Dutch prosthetic specialist and a 3D specialist who were not on site but available by email and WhatsApp Messenger (WhatsApp Inc., Menlo Park, California, USA).…”
Section: Preparing a Prosthesismentioning
confidence: 99%
“…The latter since it provides us inside in the experience of the patient concerning for example the use, sustainability and comfort of the prosthesis. This questionnaire was created earlier by Gaber et al, in 2001 to assess perceived benefits of using a certain socket for upper limb prostheses and can be found in supplement file A (Gaber et al, 2001;Van der Stelt et al, 2020). The second questionnaire was completed at the same intervals as the EQ-5D-5L questionnaire but without a null measurement.…”
Section: Data Acquisition Hrqolmentioning
confidence: 99%
See 1 more Smart Citation